(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The SARS-CoV-2 pandemic is a global health problem. The virus manifests with variable clinical outcomes, ranging from asymptomatic patients to pneumonia with adult respiratory distress and multi-organ failure. This study aims to analyze, through molecular mechanisms, whether the transcription factors activated during the response to misfolded proteins, SXBP1, maintain the transcription of genes encoding cytokines involved in the hyperinflammation associated with the cytokine storm. We studied, in nasopharyngeal samples and bronchial aspirates from patients